Hirnantian (Latest Ordovician) graptolites from the Upper Yangtze region, China - Xu, Chen (陈旭); Xuan, FJ (樊隽轩); Melchin, MJ; Mitchell, CE (WILEY-BLACKWELL, 2005)
The Upper Yangtze region yields a Hirnantian (latest Ordovician) graptolite fauna that includes 41 species assigned to 13 genera. This fauna is particularly important for understanding the Late Ordovician mass extinction event because it is the most diverse known from this interval. In addition, it records the survival, well into the Hirnantian, of many taxa of the Dicranograptidae-Diplograptidae-Orthograptidae (DDO) fauna, which was previously regarded as having gone extinct at the beginning of the Hirnantian. Taxa exhibiting six different astogenetic patterns, including taxa with reclined stipes, scandent, biserial, full-periderm and 'archiretiolitid' rhabdosome forms occur in the lower Normalograptus extraordinarius-N. ojsuensis Biozone. In contrast, in the upper N. persculptus Biozone only four genera remain, all but one of which are Normalograptidae: scandent and biserial taxa with Pattern H astogeny. Normalograptids are the dominant form of the succeeding, lower Rhuddanian, faunas. The Yangtze faunas also document the early expansion of normalograptids coeval with the decline of the DDO fauna. Many previously identified species considered endemic to China have been synonymized; 24 of the 41 species recorded here have been recognized elsewhere. No new taxa are described.